Cephalosporin graded challenges approach in community–acquired pneumonia patient with a history of penicillin allergy - Suryana, Ketut (International Journal of Research in Medical Sciences, 2021)
Community-Acquired Pneumonia (CAP) is an acute pulmonary parenchyma infection that acquired in the community. Diagnosis based on clinical manifestations, chest X-ray (CXR) and microbiological diagnosis test (lung aspirates culture). Recently there was advance in antimicrobial treatments of CAP and a microbiological diagnostic test is essential to ensure antimicrobial treatments. In the other hand microbiological diagnostic test does not achieve all of the pneumonic cases. Therefore, antimicrobial treatment should be empirically performed to avoid the delay in establishing appropriate treatment related with the mortality. By administering combination antimicrobial will achieve a better outcome than a mono-therapy. For patients with history of penicillin allergy, though the risk of cephalosporin allergic cross-reactivity is low, a greater awareness is still needed, so a graded challenge approach could be considered. Herein we present a case report of a female, 20-year-old, hospitalized due to CAP, and also had a history of penicillin allergy. She was treated by levofloxacin 750 mg IV q 24 hour and cephalosporin (ceftriaxone) 1 g IV q 12 hour with a Graded challenge approach. Although it does not a novelty, we hope it would remind the health care that a Graded challenge could be considered as an approach of administering cephalosporin in patient who has an experiece of penicillin allergy.